Reciprocal intraguild predation between two mirid predators, Cyrtorhinus lividipennis and Tytthus chinensis (Hemiptera: Miridae). Issue 9 (1st September 2016) - Qiao, Fei; Zhu, Qing-Zi; Wang, Xue-Qin; Wang, Guang-Hua; Gurr, Geoff M.; Zhu, Zeng-Rong; Heong, Kong L.; Cheng, Jia-An
ABSTRACT: Interactions between predator species shape ecological communities and are crucial in the relationship between biodiversity and ecosystem functioning. They contribute to improving the natural biological control. Cyrtorhinus lividipennis Reuter and Tytthus chinensis Stål (Hemiptera: Miridae) are important natural enemies of brown planthopper, Nilaparvata lugens Stål (Hemiptera: Delphacidae), the most destructive rice pest in Asia. Comparative functional responses of both sexes of the two mirids at different development stages were estimated and the direction, symmetry, as well as intensity of intraguild predation (IGP) were studied in the laboratory. Prey preferences of the two mirid species and the influence of alternative prey on functional responses were also evaluated. The mirids exhibited reciprocal IGP in addition to consuming eggs of BPH. All predator–prey combinations exhibited a type II functional response. Females and fourth instar nymphs of C. lividipennis showed greater voracity for eggs of BPH than of T. chinensis . The two mirids were more voracious to intraguild prey than to extraguild prey. Alternative prey released the functional responses of C. lividipennis to both intra- and extraguild prey. In contrast, alternative prey had no effect on the functional response of T. chinensis . RIGP was symmetrical in the absence of extraguild prey. And in the presence of extraguild prey that was common in the field, resulted in different responses by the mirids.